2017
DOI: 10.3389/fmars.2017.00166
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization and Vertical Distribution of Marine Gel Particles (TEP and CSP) in the Arctic Fram Strait

Abstract: Gel particles-a class of abundant transparent organic particles-have increasingly gathered attention in marine research. Field studies on the bacterial colonization of marine gels however are still scarce. So far, most studies on respective particles have focused on the upper ocean, while little is known on their occurrence in the deep sea. Here, we report on the vertical distribution of the two most common gel particle types, which are polysaccharide-containing transparent exopolymer particles (TEP) and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 47 publications
5
60
1
1
Order By: Relevance
“…Largely different prokaryote-TEP relationships between the upper and deep oceans under- score the complexity of interactions between TEP and prokaryotes. Prokaryotes can be a source of TEP as well as consumers (decomposers) of TEP and TEP precursors (Yamada et al 2013, Busch et al 2017. The prokaryotic parameters−TEP relationship may be the net outcome of opposing (i.e.…”
Section: Tep Distributions and Potential Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Largely different prokaryote-TEP relationships between the upper and deep oceans under- score the complexity of interactions between TEP and prokaryotes. Prokaryotes can be a source of TEP as well as consumers (decomposers) of TEP and TEP precursors (Yamada et al 2013, Busch et al 2017. The prokaryotic parameters−TEP relationship may be the net outcome of opposing (i.e.…”
Section: Tep Distributions and Potential Mechanismsmentioning
confidence: 99%
“…In the Mediterranean Sea, the TEP concentration was higher in deep waters (300−1000 m) than in the subsurface chlorophyll maximum layer, where most TEP were associated with prokaryotic cells (Bar-Zeev et al 2011). A recent study conducted in the Arctic Fram Strait also revealed that TEP in meso-and bathypelagic waters were colonized by prokaryotes, with densities (cell abundance per unit area of TEP) similar to those in upper waters (Busch et al 2017). This evidence suggests that TEP are potentially a significant component of the POC pool and can provide organic carbon substrates for microbial consumption in deep waters.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas it is most likely that all TEP aggregates are colonized to some extent by bacteria, some studies reported that up to 68% of total bacterial cells found in water were attached to EPS (Mari and Kiorboe 1996). A recent study suggests that this might have implications for the transport of bacterial communities between different waterbodies (Busch et al 2017). During aggregation, heterotrophic bacteria may change TEP quantity and composition by extracellular enzyme activities (Smith et al 1995) and/or uptake of TEP microgels (Taylor and Cunliffe 2017).…”
mentioning
confidence: 99%
“…These colonization processes have been studied intensively (Grossart et al, 2006b;Thiele et al, 2015;Busch et al, 2017). Interactions of bacteria with microalgae or detritus will result in a series of biochemical or physical events, which change the characteristics of the colonized particle, let it grow or shrink in size, and alter its density, porosity, stickiness, and sinking velocity (Alldredge and Youngbluth, 1985;Alldredge et al, 1986;Biddanda and Pomeroy, 1988;Kiørboe and Jackson, 2001;Kiørboe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%